Understanding human activities through 3D sensors : Second International Workshop, UHA3DS 2016, held in conjunction with the 23rd International Conference on Pattern Recognition, ICPR 2016, Cacun, Mexico, December 4, 2016, revised selected papers /: Second International Workshop, UHA3DS 2016, held in conjunction with the 23rd International Conference on Pattern Recognition, ICPR 2016, Cacun, Mexico, December 4, 2016, revised selected papers. ([2018]) - Unknown
No abstract available